Investigation of waves generated in transversely isotropic micropolar generalized thermoelastic half space under temperature dependent properties - Gupta, Raj Rani; Gupta, Rajani Rani (Zielona Góra: Uniwersytet Zielonogórski)
The present study deals with the propagation of waves in a transversely isotropic micropolar generalized thermoelastic material possessing temperature dependent elastic properties. After developing the solution for LS, GL and CT theory, the phase velocities and attenuation quality factor have been obtained. The expressions for amplitudes of stresses, displacements, microratation and temperature distribution have been derived and computed numerically. The numerically evaluated results have been plotted graphically. Some particular cases of interest have also been obtained.
Keywords: micropolar; transversely isotropic; generalized thermoelasticity; amplitude ratios